Empirical Study on the Nexus of Earnings Quality, SDG, and ESG on Malaysian Financial Institutions - Lim, Keh Yee; Mohd Sabrun, Ibrahim; Fatimah Noor Rashidah, Mohd Sofian; Sharon Cheuk, Choy Sheung; Salawati, Sahari; Joanne Shaza, Janang (2023)
When the market becomes aware of manipulation, financial organizations incur considerable losses in value, which leads to worries about the public's approval of such accounting techniques. This deliberate management practice can have a negative impact not just on shareholders and workers but also on society and the reputations of managers. As a result of the possibility that Shariah principles are ineffective in effectively creating good company management and reporting processes, Malaysian banks might not follow the same steps as in past cases. The purpose of this research is to investigate the relationship between the disclosure of Sustainable Development Goals (SDGs) and the profits management practices of public listed companies (PLCs) in the banking industry in Malaysia. The study produces new measurements on SDG disclosure and apply well-established models to detect earnings management methods in the banking sector. Both of these will be done as part of the research. The findings will be beneficial to a variety of stakeholders, including regulators, policymakers, investors, and shareholders. Additionally, the findings will serve as a reminder to businesses that they need to improve their SDGs disclosure practices in the future to avoid unethical and immoral behaviors, such as earnings management, which may lead to illegal and fraudulent activities as well as financial crime.